ANALISIS FAKTOR PERILAKU BERESIKO PENULARAN HIV/AIDS PADA PENDERITA IBU RUMAH TANGGA (IRT) DI TEMBILAHAN TAHUN 2019 - Haryati Astuti (Jurnal Kesehatan Husada Gemilang, 2022)
HIV or Human Immunodeficiency Virus is a virus that attacks the white blood cells in body (T lymphocytes). AIDS or Acquired Immune Deficiency Syndrome is a set of symptoms of disease arising due to the power imbalance. There are about 33.4 million people infected the HIV/AIDS over the world. 15.7 million (47%) of this number of people, are women and 2.1 million are kids whose ages under 15 years old. Most of the reason why housewives infected the HIV/ AIDS are infected by their husbands who are having sexual intercourse carelessly, lack of knowledge, and bad attitude and behavior. The purpose of the research is to discern the analysis of factors of risk behavior of HIV/ AIDS infection on housewives in Tembilahan, 2018. This is a qualitative descriptive research which consists of main informant (7 people) and 1 supporting informant. The method of sampling if total sampling. The results show that HIV/ AIDS is due to the risk-behavior. It is expected that this research enriches the reference for other researches, workers of community health center can detect the HIV/ AIDS early, and counselor can provide more information and counseling to risk-housewives.